2018
DOI: 10.1158/1541-7786.mcr-17-0597
|View full text |Cite
|
Sign up to set email alerts
|

Autophagic Flux Is Regulated by Interaction Between the C-terminal Domain of PATCHED1 and ATG101

Abstract: The Hedgehog (Hh) receptor Patched1 (PTCH1) is a well-known tumor suppressor that in its active form represses Smoothened (SMO) activity, inhibits proliferation, and induces apoptosis. The cytoplasmic C-terminal domain (CTD) regulates PTCH1 turnover and nucleates a pro-apoptotic complex. In this study, it was mechanistically determined that Autophagy Related 10 (ATG101), essential for mammalian autophagy, physically interacts with the CTD of PTCH1 and connects it to the ULK complex, which stimulates the autoph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…In line with the rescue experiment, miRNA-342-5p might activate fibrotic responses in the kidney by interacting with Ptch1, which is directly regulated by FoxO3. As reported previously, Ptch1 has therapeutic implications in Hh-dependent cancers by inhibiting autophagy ( Chen et al, 2018 ). Autophagy can maintain cell homeostasis and energy under different physiological states ( Klionsky, 2007 ).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In line with the rescue experiment, miRNA-342-5p might activate fibrotic responses in the kidney by interacting with Ptch1, which is directly regulated by FoxO3. As reported previously, Ptch1 has therapeutic implications in Hh-dependent cancers by inhibiting autophagy ( Chen et al, 2018 ). Autophagy can maintain cell homeostasis and energy under different physiological states ( Klionsky, 2007 ).…”
Section: Discussionsupporting
confidence: 58%
“…Autophagy mediates the development of RF, and a previous study showed that Ptch1 could inhibit autophagy in Hedgehog (Hh)-dependent cancers ( Chen et al, 2018 ). However, whether Ptch1 regulates autophagy and participates in the pathophysiological process of RF is not yet clear.…”
Section: Resultsmentioning
confidence: 99%
“…These findings suggest that B7H3 degradation is mediated by autophagy. We further showed that the levels of autophagy-related markers, LC3B-II and p62 (Cohen-Kaplan et al, 2016;Chen et al, 2018) were significantly higher and lower, respectively in IDH1-R132H U87 cells when compared to the IDH1-WT cells (Figure 3E). Similarly, a parallel results of LC3B-II and p62 was also observed in IDH1-R132H U251 cells when compared to that in IDH1-WT cells (Figure 3F), which suggests an activated autophagy flux in IDH1-R132H U87 and U251 cells compared to IDH1-WT cells.…”
Section: Autophagy Inhibition Blocks B7h3 Degradationmentioning
confidence: 81%
“…Pharmacologically, the use of GANT-61 enhances the cytotoxic effect of TMZ by the increment of acid vesicles and Beclin-1 expression ( 220 ). Furthermore, the regulatory domain of PTCH1, the main receptor of the Hedgehog pathway, interacts physically with the autophagy-related protein ATG101 in a nutrient starvation microenvironment, inhibiting the autophagic process ( 221 ). Additionally, GBM cells overexpressing the stem marker SOX3 showed an upregulation in Hh pathway activity and suppression of autophagy, leading to an increment in proliferation and invasion ( 222 ).…”
Section: Autophagy Activation As a Response To Internal Stimulimentioning
confidence: 99%